Выражение (4sina - 3cosa)^2 + (3sina + 4cosa)^2

Nastena11102003 Nastena11102003    2   04.09.2019 20:20    1

Ответы
Pollyru Pollyru  06.10.2020 17:52
(4sinA - 3cosA)² + (3sin²A + 4cos²A) = 16sin²A - 24sinAcosA + 9cos²A +
+ 9cos²A + 24sinAcosA + 16sin²A = 25sin²A + 25cos²A = 25(sin²A + cos²A) =  
= 25
ПОКАЗАТЬ ОТВЕТЫ
makusolka makusolka  06.10.2020 17:52
(4sinA - 3cosA)^2 + (3sinA + 4cosA)^2=
=16sin²A-24sinAcosA+9cos²A+9sin²A+24sinAcosA+16cos²A=
=25(sin²A+cos²A)=25*1=25
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра